Use of the Handgrip Strength Test in the Identification of Osteosarcopenic Obesity in Older Women: A Prospective Study - Dos Santos, Vanessa Ribeiro [UNESP]; Gobbo, Luís Alberto [UNESP] (Wolters Kluwer, 2020)
The aim this study was to analyze the sensitivity and specificity of functional tests in the identification of osteosarcopenic obesity (OSO), as well as other abnormalities related to low bone mineral density in older women in 24-month follow-up. The study included 152 older women. It was observed that the handgrip strength test presented sensitivity and specificity to identify OSO (0.63 and 0.76), respectively, and that older women with low performance in this test had a higher risk (hazard ratio: 3.05; 95% confidence interval: 1.04-8.96) of presenting OSO. The application of the handgrip strength test could be an alternative instrument for identification of OSO in older women.
Keywords: obesity; osteoporosis; physical function; sarcopenia